A systematic review of eHealth interventions to improve health literacy. (June 2016) - Jacobs, Robin J; Lou, Jennie Q; Ownby, Raymond L; Caballero, Joshua
Implementation of eHealth is now considered an effective way to address concerns about the health status of health care consumers. The purpose of this study was to review empirically based eHealth intervention strategies designed to improve health literacy among consumers in a variety of settings. A computerized search of 16 databases of abstracts (e.g. Biomedical Reference Collection, Cochrane Central Register of Controlled Trials, Computers & Applied Sciences Complete, Health Technology Assessments, MEDLINE) were explored in a systematic fashion to assess the presence of eHealth applications targeting health literacy. Compared to control interventions, the interventions using technology reported significant outcomes or showed promise for future positive outcomes regarding health literacy in a variety of settings, for different diseases, and with diverse samples. This review has indicated that it is feasible to deliver eHealth interventions specifically designed to improve health literacy skills for people with different health conditions, risk factors, and socioeconomic backgrounds.